POTENSI PENERAPAN NILAI-NILAI BUDAYA LOKAL PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Mimin Minawati (Jurnal Math-UMB.EDU, 2020)
The purpose of this study is to see and explain the potential application of local cultural values to the learning process in elementary schools. Problems that occur based on the results of observations that many students have difficulty in understanding mathematical concepts, so that it will affect student learning outcomes. The method in this research uses the type of case study research. The sample of this study was 3 (three) elementary schools in Jakarta. Some types of local culture that are applied consist of 2 (two) types, namely Textual and Building. The results of the study were conducted in several schools, namely the Mathematics learning process using local culture-based learning models such as doorstop learning models and teachers using media and local culture-based teaching aids such as miniature Betawi traditional houses. By integrating Local Wisdom in Mathematics learning, mathematical objects that exist in the human mind, in the form of facts, concepts, principles, and skills will emerge so as to strengthen the ability of understanding, reasoning, creative, critical, and communicative in solving mathematical problems faced by students.Keywords: Local Cultural Values; Mathematics Learning